Accommodation of the human lens capsule using a finite element model based on nonlinear regionally anisotropic biomembranes. Issue 3 (17th February 2017) - David, G.; Pedrigi, R. M.; Humphrey, J. D.
Abstract : Accommodation of the eyes, the mechanism that allows humans to focus their vision on near objects, naturally diminishes with age via presbyopia. People who have undergone cataract surgery, using current surgical methods and artificial lens implants, are also left without the ability to accommodate. The process of accommodation is generally well known; however the specific mechanical details have not been adequately explained due to difficulties and consequences of performing in vivo studies. Most studies have modeled the mechanics of accommodation under assumptions of a linearly elastic, isotropic, homogenous lens and lens capsule. Recent experimental and numerical studies showed that the lens capsule exhibits nonlinear elasticity and regional anisotropy. In this paper we present a numerical model of human accommodation using a membrane theory based finite element approach, incorporating recent findings on capsular properties. This study seeks to provide a novel perspective of the mechanics of accommodation. Such findings may prove significant in seeking biomedical solutions to restoring loss of visual power.